Effect of interactive multimedia learning to learn skills of students sports volleyball - Gunawan, Gunawan; Firmansyah, Dlis; Widiastuti, Widiastuti (Journal of Education, Health and Sport, 2019)
Introduction. Mastery of basic technical skills of volleyball is the basis of learning theory and practice volleyball at sports students. The rapid development of instructional media, both software, and hardware which will surely bring a shift in the role of educators as a messenger, than that used to principle-centered learning educators to student-centered learning. Likewise, the tendency of increasing student technology literacy. What was once a student-centered learning please educators, students now want them given the widest possible opportunity for independent study with a variety of media sources and learning?The objective of the work. This study aims to determine whether the basic technical skills learning model based interactive multimedia volleyball effectively improve the basic techniques of volleyball skill sports student.Research methods. Quantitative research with Quasi-Experiment. The design was pretest-posttest non-equivalent control group design. Subjects in the study were students of sportsResearch result, Based on data analysis of N-Gain score through independent test sample t-test is known sig (2-tailed) was 0.000 <0.05Conclusions. There was a significant difference in the effectiveness of the (real) between the usage-based model of learning volleyball interactive multimedia with conventional learning models to improve learning outcomes of basic technical skills students volleyball sport.